A comparison of biomedical activities components in ulams using gc-ms / Aisyah Ismail - Ismail, Aisyah (Faculty of Applied Sciences, 2017)
In this study, the biomedical activities components in ulams have been analyzed using GC-MS. The chemical compositions of the plant extracts were studied using Perkin-Elmer GC-MS, to determine which ulam has the highest biomedical activities components. The result shows that, Cosmos caudatus has the highest number of biomedical activities compounds with 12 compounds. Followed by, Oenanthe javanica (11 compounds), Parkia speciosa (beans) has 9 main compounds, Parkia speciosa (pods) and Centella asiatica has 8 main compounds and and Piper sarmentosum has 4 major compounds. GC-MS analysis revealed the biomedical activities compounds in Cosmos caudatus are cycloheptasiloxane, cyclooctasiloxane, cyclononasiloxane, cyclodecasiloxane, cyclohexasiloxane, hexadecanoic acid, Bis(pentamethylcyclotrisiloxy)tetramethyldisiloxane, 2-Pentadecanone, 6,10,14-trimethyl-, (1R,7S,E)-7-Isopropyl-4,10-dimethylenecyclodec-5-enol, glycylsarcosine, 5H-Cyclopropa[3,4]benz[1,2-e]azulen-5-one,9-(acetyloxy)-3-[(acetyloxy)methyl]-1, 1a, 1b, 4, 4a, 7a, 7b, 8, 9, 9a-decahydro-4a,7b,9a-trihydroxy-1,1,6,8-tetramethyl-, 7-Methylthioheptanenitrile, N-(2-Phenylethyl)undeca-(2Z,4E)-diene-8,10-diynamide, estra-1,3,5(10)-trien-17β-ol and caryophylla-4(12),8(13)-dien-5α-ol.